Clinical and Economic Expedience of Ertapenem Therapy of Complicated Urinary Tract Infection - A. S. Kolbin; S. V. Sidorenko; K. A. Zagorodnikova; V. B. Musatov; A. A. Yakovlev (Антибиотики и Химиотерапия)
Clinical and economic investigation of various antibiotics use in the treatment of complicated urinary tract infection (CUTI) was performed under the Russian economic environment. The drugs of comparison were ertapenem, ceftriaxone and levofloxacin. Direct costs and their structure were shown, and the cost efficiency was calculated. Alternative analysis and one-side susceptibility analysis were performed. In complicated urinary tract infections when the major pathogens were Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis it was clinically and economically reasonable to start the treatment with ceftriaxone or ertapenem, while levofloxacin could be an alternative strategy. When the effects of the acquired resistance on the treatment effectiveness were evaluated (SIS model) it was shown that the pathogens susceptibility to ertapenem was preserved for a significantly longer time than that to ceftriaxone or levofloxacin (60 months). Such a parameter may serve as an additional evidence of the reasonable use of ertapenem as the starting treatment of CUTI.